(untitled) (Fiep Bulletin - online, 2014)
A study on the relative influences of the environment, variation of weight, index of corporal mass (IMC) of twin of masculine and feminine sex with ages of 1 the 39 years, the cities of Good Jesus and Currais-PI. It was carried through by the method of twin through the herdabilidade index (h²). The studied sample was constituted by 9 pairs of Mz twin and 11 pairs of Dz. twin Only for the corporal weight and the IMC had not been found estatisticamente significant differences between the variances of the monozigoticos and dizigoticos groups. For the excessively changeable ones it was possible to infer that human being exists also ambient significant genetic influence as. These 0 variable present herdabilidade indices elevados(h²=0,84 0,93),que confirm the importance of if considering the paper of the genetic influence on the antropométricas characteristics mainly how much to the environment. Through the dermatoglifia with the use of the fingerprints as a light in the discovery of talentos, it is characterized as a genetic marker of ample specter for the use in association with basic the physical qualities in the discovery of talentos for practical the porting one in diverse modalities that in offer a varied set to them of benefits that a long specter in the biological domain to the psychological one covers.